2021
DOI: 10.1186/s43042-021-00131-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrilin-1 (MATN1) polymorphism in class III skeletal malocclusion with mandibular prognathism in Deutero-Malay race: a case-control study

Abstract: Background Several studies have identified different genes that control the final dimension and structure of the mandible. Prognathism of the mandible is thought to correlate with these genes; however, no specific gene has been assigned as a risk factor due to various genome-wide scan results in different races. Previous studies that involved the Han ethnic group in China and Korea suggested matrilin-1 (MATN1) polymorphism as the contributor for mandibular prognathism. To date, no study has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This result agreed with the preventive effect described in a human study on the presence of the AA genotype of rs20566 (Jang et al, 2010), and was in line with the association of rs1149042 with mandibular retrognathism (Balkhande et al, 2018). In contrast, other human studies have shown an increased risk of mandibular prognathism in the presence of rs1065755 and an association of MATN1 with SCIII malocclusion in Korean (Jang et al, 2010), Indian (Kulkarni et al, 2021), and Deutero‐Malay (Laviana et al, 2021) populations. Similar results were observed for MYO1H (GOC:100/100; WGA:60.8/100) coding for unconventional myosin‐Ih APD:1.05), in which an increased risk of presenting with MP in the presence of rs3825393, a non‐synonymous common variant, C > T, p. Pro1001Leu, was reported by Sun et al in a knockdown zebrafish model (Sun et al, 2018).…”
Section: Resultsmentioning
confidence: 85%
“…This result agreed with the preventive effect described in a human study on the presence of the AA genotype of rs20566 (Jang et al, 2010), and was in line with the association of rs1149042 with mandibular retrognathism (Balkhande et al, 2018). In contrast, other human studies have shown an increased risk of mandibular prognathism in the presence of rs1065755 and an association of MATN1 with SCIII malocclusion in Korean (Jang et al, 2010), Indian (Kulkarni et al, 2021), and Deutero‐Malay (Laviana et al, 2021) populations. Similar results were observed for MYO1H (GOC:100/100; WGA:60.8/100) coding for unconventional myosin‐Ih APD:1.05), in which an increased risk of presenting with MP in the presence of rs3825393, a non‐synonymous common variant, C > T, p. Pro1001Leu, was reported by Sun et al in a knockdown zebrafish model (Sun et al, 2018).…”
Section: Resultsmentioning
confidence: 85%
“…One possibility is that for each of these four genes, different SNPs may lead to a more active isoform or higher expression in one class malocclusion and a more inert isoform or less expression in the other. However, available GWAS studies [ 30 , 34 , 35 , 38 , 40 , 43 , 46 , 47 , 48 , 53 , 54 ] revealed that certain SNPs, including rs2249492 ( COL1A1 ), rs11200014 ( FGFR2 ), rs2162540 ( FGFR2 ), rs10850110 ( MYO1H ), and rs3825393 ( MYO1H ), were shared by skeletal class II and class III malocclusions ( Table 7 ), which cannot be explained by the hypothesis mentioned above. Surprisingly, most of the reported skeletal class II or class III malocclusion-associated SNPs are located in the introns of these four genes [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], indicating the importance of the noncoding regions of these DNA fragments in craniofacial development and skeletal malocclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In a different study (Kulkarni et al, 2020), albeit somewhat constrained by a small sample size, rs20566 and frameshift variants at rs1065755 exhibited notably higher frequencies in 35 skeletal Class III patients with mandibular prognathism compared to 30 control individuals from an Indian population. By studying the MATN1 gene's association with mandibular prognathism in the Deutero-Malay race in Indonesian subjects, Laviana et al (2021) indicate that polymorphism of exon 5 regions of the MATN1 gene, 354 T>C (rs20566) CC genotype, is the risk factor of such craniofacial disorder. In this case no CC genotype was identified in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Given the correlation of multiple single nucleotide polymorphisms (SNPs) with malocclusion, this paper focuses on the rs1065755 polymorphism (8572 C>T), which has been associated with an elevated risk of mandibular prognathism in Korean population (Jang et al, 2010). Other studies address the potential genetic predisposition linked to the MATN1 gene in various dental conditions across populations primarily from India (Rathod et al, 2023, Balkhande et al, 2018, Korea (Yamaguchi et al, 2005), and Indonesia (Laviana et al, 2021), leaving the European space a less explored territory.…”
Section: Introductionmentioning
confidence: 99%